2020
DOI: 10.3390/agriculture10110531
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Effects on Cotton Performance and Soil Quality in an Irrigated Arid Cropping System

Abstract: Reducing tillage has become necessary in irrigated, arid cropping systems in southwestern USA, to address soil degradation and erosion problems associated with intensive soil tillage. A study was conducted in arid southwestern USA, to compare a reduced tillage method (strip tillage) to two conventional tillage methods (plow tillage and raised bed tillage) for irrigated upland cotton (Gossypium hirsutum) production. Strip tillage (ST) was established in a single pass by a strip tillage equipment, while the plow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The yield response of fiber crops was positive only with MO under NT (1.8%), even if this result is limited due to a very small sample size (n = 2), in accordance with the findings of Idowu et al [98] that reported several benefits of reduced tillage in cotton crop. Moreover, oilseeds and root crops showed a significant increase in grain yield using O with CT (21.8%) and MO with CT and RT (18.8 and 16.2%, respectively).…”
Section: Crop Categoriessupporting
confidence: 90%
“…The yield response of fiber crops was positive only with MO under NT (1.8%), even if this result is limited due to a very small sample size (n = 2), in accordance with the findings of Idowu et al [98] that reported several benefits of reduced tillage in cotton crop. Moreover, oilseeds and root crops showed a significant increase in grain yield using O with CT (21.8%) and MO with CT and RT (18.8 and 16.2%, respectively).…”
Section: Crop Categoriessupporting
confidence: 90%
“…The soil tillage operated with different machineries could affect positively the water holding, increasing the incorporation of crop residues in the soil surface with higher water content in the upper soil layer and lower evapotranspiration, lower soil temperature, and more stable soil aggregates, protection of soil erosion, nutrients and organic C accumulation near the soil surface, nitrogen leaching decreased [7]. Most of the crop cultivation came with intensive tillage operations using plow and disk harrow as primary and secondary tillage equipment with multiple fields passes to create a suitable seedbed for crop cultivation [8]. Although soil tillage had a positive influence on crop performance, intensive tillage could cause adverse effects on soil fertility [9].…”
Section: Introductionmentioning
confidence: 99%